(untitled) (TAMADDUN NURI JURNALI, 2024)
This article deals with analyses of multifaceted character of Sohibqiron in the work of “Ulug’ Saltanat” by Muhammad Ali and there will be a thorough examination of Amir Temur’s depiction. The piece will investigate how the author represents the historical figure Amir Temur, characterized by his complexity and enigma.